The Impact of Malnutrition on 30-Day Postoperative Complications following Surgical Fixation of Distal Radius Fractures - Newman, Jared M.; Coste, Marine; Dua, Karan; Yang, Andrew; Cautela, Frank S.; Shah, Neil V.; Patel, Aakash M.; Chee, Alexander; Khlopas, Anton; Koehler, Steven M. (Journal of Hand and Microsurgery, 2020)
Introduction Distal radius fractures (DRFs) are increasingly managed surgically among fragility fractures due to prolonged life expectancy and surgical advancements. Yet, malnutrition can impact postoperative outcomes and complications. We sought to determine the impact of malnutrition on open reduction and internal fixation (ORIF) of DRFs during the perioperative and 30-day postoperative periods.Materials and Methods Using the National Surgical Quality Improvement Program database, all patients who underwent ORIF of a DRF between January 1, 2008, and December 31, 2016, were identified and stratified by preoperative serum albumin levels: normal (≥3.5 g/dL; n = 2,546) or hypoalbuminemia (<3.5 g/dL; n = 439). Demographical and perioperative data were compared. Operative complications were stratified into major and minor complications, and data were analyzed using descriptive statistics and multivariate regression models.Results Compared with patients with normal levels, a higher proportion of hypoalbuminemia patients had ASA scores > 3 (9.1 vs. 2%) and a longer mean length of stay (3.16 vs. 0.83 days). Hypoalbuminemia patients also had 625% greater odds for developing major complications during the 30-day postoperative period (odds ratio = 7.25; 95% confidence interval: 1.91–27.49).Conclusion Malnutrition significantly affected outcomes and complications of distal radius ORIF. This study highlights the importance of prevention and treatment of malnutrition in the setting of fragility fractures.
Keywords: distal radius fracture; fragility; hypoalbuminemia; malnutrition; open reduction internal fixation; complications; surgical fixation